Analysis of Added Value of Aromatic Components of Robusta Coffee Flowers (Coffea canhephora) in Lampung - Fahrulsyah; Utomo, Tanto Pratondo; Suroso, Erdi; Subeki; Hidayati, Sri (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2021)
This study aims to analyze the added value of the aromatic component of Robusta coffee flowers in Lampung Province. The research method is done by descriptive analysis. There are three extraction processes in this research, after obtaining the oil yield from each extraction, one method is chosen to produce the best oil aroma and its added value is analyzed. Calculation of added value using the Hayami method for analysis. The yield of fragrance that most closely resembles natural coffee flowers will be calculated on the analysis of added value or benefits. Based on organoleptic tests, the aroma that most closely resembles natural coffee flowers is coffee flowers extracted by a rotary evaporation method in which the raw material for coffee flowers is taken / harvested in the phase before pollination (yield of 16.1%). The added value of processing aromatic extracts of coffee flowers (Rotary Evaporation method) with raw materials as much as 1 kg, which is IDR 933,923 and obtained a ratio value of 82.3%. The added value of this aromatic component of coffee flowers falls into the high category (> 40%). The profit gained one time production of coffee flowers into coffee flower oil is IDR 553.923 with a profit rate of 59,3 %.